2013
DOI: 10.4049/jimmunol.1202033
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the TLR2/6 Transmembrane Domains Is Essential for Activation and Is a Target for Prevention of Sepsis

Abstract: TLR2, together with TLR1 and TLR6, is essential for detecting lipopeptides and bacterial cell wall components such as lipoteichoic acid from Gram-positive bacteria. In this study, we report that transmembrane domain (TMD)–derived peptides from TLR2 and TLR6 specifically inhibit TLR2 activation. Secretion of the cytokines TNF-α and IL-6 by cultured macrophages (RAW264.7 cell line) was inhibited by these peptides in response to TLR2 activation by lipoteichoic acid (TLR2/6 activator) or palmitoyl (3)-Cys-Ser-Lys(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…All human TLR TMD constructs exhibited strong homotypic interactions, whilst TLR2 formed stable heterodimers only with their associated subfamily members, TLR1, TLR6 and TLR10 [75], consistent with their biologically relevant roles in ligand recognition discussed above, and with their high sequence identities of ~50-90%. Further biochemical and biophysical assays showed that exogenous synthetic peptides of mouse TLR2 and TLR6 TMDs, expressed in macrophages, affect TLR2 activation by inhibiting TNF-α secretion upon stimulation by lipoteichoic acid, a TLR2/6 activator from Grampositive bacteria [5]. These studies confirmed heterodimerization and strong associated heterotypic interactions between the TLR2 and TLR6 TMDs.…”
Section: Tlr Transmembrane Domainssupporting
confidence: 61%
See 3 more Smart Citations
“…All human TLR TMD constructs exhibited strong homotypic interactions, whilst TLR2 formed stable heterodimers only with their associated subfamily members, TLR1, TLR6 and TLR10 [75], consistent with their biologically relevant roles in ligand recognition discussed above, and with their high sequence identities of ~50-90%. Further biochemical and biophysical assays showed that exogenous synthetic peptides of mouse TLR2 and TLR6 TMDs, expressed in macrophages, affect TLR2 activation by inhibiting TNF-α secretion upon stimulation by lipoteichoic acid, a TLR2/6 activator from Grampositive bacteria [5]. These studies confirmed heterodimerization and strong associated heterotypic interactions between the TLR2 and TLR6 TMDs.…”
Section: Tlr Transmembrane Domainssupporting
confidence: 61%
“…These studies confirmed heterodimerization and strong associated heterotypic interactions between the TLR2 and TLR6 TMDs. Moreover, in vivo studies have demonstrated the potential for therapeutic targeting by TMDs, by showing that these peptide constructs could inhibit TLR2 activation, reducing lethal inflammation in mice [5].…”
Section: Tlr Transmembrane Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, peptides composed of D-amino acids are being used as a tool to study TMD-TMD interactions of membrane-embedded receptors, as in the case of the glycophorin A and the bacterial aspartate receptor (33,46). Furthermore, exogenously added TMD peptides can be used to investigate the assembly of membrane proteins in vivo by interacting with their corresponding segments within the membrane (43,(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%